Foregut organ progenitors and their niche display distinct viscoelastic properties in vivo during early morphogenesis stages - Dzementsei, Aliaksandr; Barooji, Younes F.; Ober, Elke A.; Oddershede, Lene B. (Communications Biology, 2022)
Material properties of living matter play an important role for biological function and development. Yet, quantification of material properties of internal organs in vivo, without causing physiological damage, remains challenging. Here, we present a non-invasive approach based on modified optical tweezers for quantifying sub-cellular material properties deep inside living zebrafish embryos. Material properties of cells within the foregut region are quantified as deep as 150 µm into the biological tissue through measurements of the positions of an inert tracer. This yields an exponent, α, which characterizes the scaling behavior of the positional power spectra and the complex shear moduli. The measurements demonstrate differential mechanical properties: at the time when the developing organs undergo substantial displacements during morphogenesis, gut progenitors are more elastic (α = 0.57 ± 0.07) than the neighboring yolk (α = 0.73 ± 0.08), liver (α = 0.66 ± 0.06) and two mesodermal (α = 0.68 ± 0.06, α = 0.64 ± 0.06) progenitor cell populations. The higher elasticity of gut progenitors correlates with an increased cellular concentration of microtubules. The results infer a role of material properties during morphogenesis and the approach paves the way for quantitative material investigations in vivo of embryos, explants, or organoids.
Created from Fastlane, Scopus look-up